PTU-085 A dedicated service improves the accuracy of barrett's oesophagus surveillance: a prospective comparative cohort study. (8th June 2018) - Britton, James; Chatten, Kelly; Riley, Thomas; Cairns, Alastair; Prasad, Neeraj; Keld, Richard; Hamdy, Shaheen; Mclaughlin, John; Ang, Yeng
Abstract : Introduction: This study aims to assess the quality of current Barrett's Oesophagus surveillance delivery against a dedicated service in the post BSG guideline era. Methods: All patients undergoing BO surveillance between January 2016 and July 2017 at a single NHS district general hospital (DGH) were included. Patients had their endoscopy conducted on a dedicated BO endoscopy list or a generic service list. Data were collected prospectively against the BSG guidelines. Prospective surveillance data were also compared to each patient's prior surveillance endoscopy experience. Results: 361 patients were scheduled for surveillance of which 217 attended a dedicated list (29 discharged, 13.4%), 78 attended a non-dedicated list (7 discharged, 9%) and 66 did not have their endoscopy. The cohorts were comparable in terms of age, sex and co-morbidity prevalence. The dedicated list adhered more closely to the BSG guidelines (table 1). Histology results from the dedicated list cohort revealed higher rates of intestinal metaplasia (79.8% vs 73.1%, p=0.1155) and dysplasia/OAC (4.3% vs 2.6%, p=0.4082) when compared to the non-dedicated, although statistical significance was not reached. Conclusions: The post-BSG guideline era of BO surveillance remains suboptimal in this DGH. A dedicated service can improve the accuracy and consistency of surveillance care pathways in line with current best practice, although the clinical significance of this remains to be determined.